Jaarverslag 1996 Jan van Eyck Akademie. - Kuijpers, Els; van Toorn, Jan; Jan van Eyck Akademie, Maastricht (Maastricht : Jan Van Eyck Akademie, 1996)
Benoit, Alain ; Cazin, Marie-Laure ; de Clean, Claudie ; Davolio, Cesare ; Giustina, Cristina Della ; Gobyn, Luk ; Hazekamp, Risk ; Heezen, Sander ; Mew, Charlotte ; Nerinckx, Erik ; Oberdanner, Annelies ; Rogiers, Peter ; Rosenberger, Isa ; Rürup, Susanne ; Schweiger, Constanze ; Shadbolt, Matthew ; Tang, Sikay ; Thys, Harald ; Trenkel, Karin ; Benlaloua, Samira ; van Bennekom, Jop ; Bertus, Anne ; Biersteker, Niels ; Borck, Daniel ; Buissant, Jan-Maarten ; Burbulla, Marion ; Credland, Tony ; van der Giessen, Henk ; Giza, Aleksandra ; Heller, Lars ; Pick, Elizabeth ; Sandhaus, Louise ; Snelting, Fenmke ; van der Velden, Daniël ; van Vugt, Evelien ; Behrens, Roger ; Confetti, Donna ; Gerstmeier, Reinhard ; Gould, Polly ; Halgmann, Anke Haarmann Birgit ; Kouteinikova, Inesa ; Lemke, Harald ; Ogawa, Masato ; Prado, Elena ; Prinsen, Irène ; Seelig, Thomas ; Siitari, Pirkko ; Sijbring, Riek ; Turner, Renée ; Vasic, Zoriça ; Visch, Valentijn
Nederlands
boek